The contribution of bile acid metabolism to the pathogenesis of Clostridioides difficile infection - Mullish,BH; Allegretti,JR (Therapeutic Advances in Gastroenterology, 2021)
Clostridioides difficile infection (CDI) remains a major global cause of gastrointestinal infection, with significant associated morbidity, mortality and impact upon healthcare system resources. Recent antibiotic use is a key risk factor for the condition, with the marked antibiotic-mediated perturbations in gut microbiome diversity and composition that underpin the pathogenesis of CDI being well-recognised. However, only relatively recently has further insight been gained into the specific mechanistic links between these gut microbiome changes and CDI, with alteration of gut microbial metabolites – in particular, bile acid metabolism – being a particular area of focus. A variety of in vitro, ex vivo, animal model and human studies have now demonstrated that loss of gut microbiome members with bile-metabolising capacity (including bile salt hydrolases, and 7-α-dehydroxylase) – with a resulting alteration of the gut bile acid milieu – contributes significantly to the disease process in CDI. More specifically, this microbiome disruption results in the enrichment of primary conjugated bile acids (including taurocholic acid, which promotes the germination of C. difficile spores) and loss of secondary bile acids (which inhibit the growth of C. difficile, and may bind to and limit activity of toxins produced by C. difficile). These bile acid changes are also associated with reduced activity of the farnesoid X receptor pathway, which may exacerbate C. difficile colitis throughout its impact upon gut barrier function and host immune/inflammatory response. Furthermore, a key mechanism of efficacy of faecal microbiota transplant (FMT) in treating recurrent CDI has been shown to be restoration of gut microbiome bile metabolising functionality; ensuring the presence of this functionality among defined microbial communities (and other ‘next generation’ FMT products) designed to treat CDI may be critical to their success. &